Growing richer and taller: Explaining Change in the Distribution of Child Nutritional Status during Vietnam's Economic Boom - Owen O'Donnell; Ángel López Nicolás; Eddy van Doorslaer (Tinbergen Institute, 2007)
Over a five-year period in the 1990s Vietnam experienced annual economic growth of more than 8% and a decrease of 15 points in the proportion of children chronically malnourished (stunted). We estimate the extent to which changes in the distribution of child nutritional status can be explained by changes in the level and distribution of income, and of other covariates. This is done using data from the 1993 and 1998 Vietnam Living Standards Surveys and a flexible decomposition technique that explains change throughout the complete distribution of child height. One-half of the decrease in the proportion of children stunted is explained by changes in the distributions of covariates and 35% is explained by change in the distribution of income. Covariates, including income, explain less of the decrease in very severe malnutrition, which is largely attributable to change in the conditional distribution of child height.
Keywords: I12; I31; O53; 330; Malnutrition; child height; decomposition; quantile regression; Vietnam; Unterernährung; Gesundheit; Einkommensverteilung; Wirtschaftswachstum; Dekompositionsverfahren; Regression; Vietnam